Hubungan Durasi Screen Time, Konsentrasi Siswa, dan Kemampuan Membaca Pemahaman pada Siswa Kelas IV SD - Azka, Maulida Fikrotul; Irvan, Moh. Farizqo (Paedagogie, 2026)
The increasing use of gadgets among elementary school children raises concerns about its impact on learning concentration and reading comprehension skills. This study aims to determine the relationship between screen time duration and student concentration (sustained attention) with the reading comprehension skills of fourth-grade students at Gugus Wijayakusuma Elementary School, Ngaliyan District, Semarang City, in the 2025/2026 academic year. This study used a quantitative correlational design approach, involving 149 students as samples. Data collection was conducted through a screen time duration questionnaire, a Continuous Performance Test (CPT) to measure sustained attention, and a reading comprehension test. Then, correlation analysis was performed using the Spearman rho correlation test with the help of IBM SPSS 26 software. The results showed that there was an inverse relationship: when screen time was high, reading comprehension skills were low, and when screen time was high, student concentration was also low. There was also a direct relationship between student concentration and reading comprehension ability; when student concentration was high, reading comprehension ability was also high. Therefore, it can be concluded that screen time is related to reading comprehension ability both directly and indirectly through student concentration. Therefore, it is recommended that schools, teachers, and parents work together to limit and manage the use of electronic divices wisely, improve students concentration, and promote literacy habits to support the improvement of reading comprehension skills among elementary.